YES Program Book - Youth Employment Services (YES) (2020)
issued: September, 2020/December, 2020

Program Book - Youth Employment Services (YES) (2020)
issued: January, 2020/December, 2020

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Quebec Employment Service Providers Conference (2008)

Congrès des Fournisseurs de Sercices d'emploi du Québec (2008)

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)
issued: January, 2017/August, 2017

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)
issued: January, 2016/August, 2016

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)
issued: January, 2018/August, 2018

Program Book - Youth Employment Services (YES) (2013)
issued: Winter, 2013/Spring, 2013

The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Who We Are - Youth Employment Services (YES) (2020)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)
Number of pages: 1

YES E-News Monthly - Youth Employment Services (YES)
Number of pages: 1

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)
Number of pages: 4

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)
Number of pages: 2

Making your Job Search Work for You - Youth Employment Services (YES)

Fall 2016: Program Book : September 2016 - December 2016 - Youth Employment Services (YES) (2016)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Winter/Spring 2013 Program Book - Youth Employment Services (YES) (2013)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

9th Quebec Employment Service Providers Conference : The Greatest Challenges and Best Practices of Employment Service Professionals - Youth Employment Services (YES) (2011)

The 10th Annual YES Entrepreneurship Conference : YES, The Future is Yours : Workshops - Youth Employment Services (YES)

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)

The 19th Annual Entrepreneurship Conference - Youth Employment Services (YES)

6th Montreal Self-Employed Artists Conference - Youth Employment Services (YES) (2006)

YES' Artists' Conference: Business Skills for Creative Souls - Youth Employment Services (YES) (2013)